A formação docente no curso de pedagogia da Faculdade de Educação de Crateús: reflexões sobre a pesquisa monográfica - Madureiro, Maria do Carmo Carvalho (2012)
This study examines the formative character of monographic research activity of the pedagogy course at the Faculty of Education Crateús - FAEC / UECE. National Curriculum Guidelines (DCN) conceive a comprehensive proposal for the formation of a degree in Pedagogy. This theme firm in the Brazilian educational scenario as discussion agenda of the new course curriculum. Among the issues brought to reflection highlights are those who understand teaching as the basis for training in pedagogy courses. Based on the characteristics of the object of research there has been a case study as a qualitative methodological resource. In the data collection used a semi-structured interview with students and graduates of conclusive pedagogy course of FAEC / UECE and documents pertaining to this. The categories are based, in order to understand the contribution of research as teacher training and the development of teaching practice and as a field that produces knowledge itself, supported by the theories of education. Regarding the formative dimension of monographic research in teacher education, it is concluded that a joint is required and a payment structure of the course curriculum. One can think of the stage-research part of the project of institutional course, linking theory and practice continuously, where the task of the input stage has to break disciplinary boundaries in the pedagogy course. Furthermore, it is proposed also that an assessment is made of the first class of graduates of the new curriculum.